Emotions in Code (IntechOpen, 2026)
What happens when machines start to understand—maybe even feel—our emotions? Emotions in Code - The AI Frontier of Sentiment Analysis explores the fascinating intersection of artificial intelligence and human emotions. As algorithms become more sophisticated, they are learning not just to process data but to, in effect, read between the lines—interpreting tone, mimicking affect, and reacting to our moods in real-time. In a world increasingly shaped by AI, grasping how these systems interpret sentiment is not just useful—it is vital. The call for emotional intelligence in our technologies echoes louder than ever. Addressing this urgent need, the book provides: • A layered exploration of sentiment analysis, from paradoxical challenges to emerging “empathy” algorithms. • A look at the machine learning methods behind emotional recognition in language, voice, and behavior. • Case studies and insights from across the globe, spanning media, healthcare, finance, and more. • Reflections on the ethical stakes of emotional AI—what it means for trust, communication, and the human experience. Blending technical depth with real-world relevance, this book caters to researchers, developers, and anyone curious about how machines are becoming smarter at reading us, and what that means for the future.